Regulation of the iron-deficiency response by IMA/FEP peptide - Tabata, Ryo (Frontiers in Plant Science, 2023)
Iron (Fe) is an essential micronutrient for plant growth and development, participating in many significant biological processes including photosynthesis, respiration, and nitrogen fixation. Although abundant in the earth's crust, most Fe is oxidized and difficult for plants to absorb under aerobic and alkaline pH conditions. Plants, therefore, have evolved complex means to optimize their Fe-acquisition efficiency. In the past two decades, regulatory networks of transcription factors and ubiquitin ligases have proven to be essential for plant Fe uptake and translocation. Recent studies in Arabidopsis thaliana (Arabidopsis) suggest that in addition to the transcriptional network, IRON MAN/FE-UPTAKE-INDUCING PEPTIDE (IMA/FEP) peptide interacts with a ubiquitin ligase, BRUTUS (BTS)/BTS-LIKE (BTSL). Under Fe-deficient conditions, IMA/FEP peptides compete with IVc subgroup bHLH transcription factors (TFs) to interact with BTS/BTSL. The resulting complex inhibits the degradation of these TFs by BTS/BTSL, which is important for maintaining the Fe-deficiency response in roots. Furthermore, IMA/FEP peptides control systemic Fe signaling. By organ-to-organ communication in Arabidopsis, Fe deficiency in one part of a root drives the upregulation of a high-affinity Fe-uptake system in other root regions surrounded by sufficient levels of Fe. IMA/FEP peptides regulate this compensatory response through Fe-deficiency-triggered organ-to-organ communication. This mini-review summarizes recent advances in understanding how IMA/FEP peptides function in the intracellular signaling of the Fe-deficiency response and systemic Fe signaling to regulate Fe acquisition.